Islamic Social Accountability of Bank Nano Syariah: A Shariah Enterprise Theory Perspective - Faozi Fimansyah; Ahmad Roziq; Ririn Irmadariyani (International Journal Labs, 2026)
This study aimed to analyze the implementation of Islamic social accountability at Bank Nano Syariah from the perspective of Shariah Enterprise Theory using the Islamic Social Reporting (ISR) framework. A qualitative case study approach was employed. The study was based on the 2024–2025 annual reports and financial statements of Bank Nano Syariah. Data were collected and analyzed from the company's published reports during the study period. Qualitative content analysis was conducted using 43 Islamic Social Reporting (ISR) disclosure indicators across six dimensions: financing and investment, products and services, employees, community, environment, and corporate governance. Each disclosure indicator was evaluated using a dichotomous scoring method, in which disclosed items received a score of 1 and undisclosed items received a score of 0. The overall ISR disclosure level was then calculated as a percentage and interpreted according to the established disclosure categories. The results indicated that Bank Nano Syariah disclosed 24 of the 43 ISR indicators, resulting in an ISR disclosure level of 55.81%, which was classified as moderate. The highest level of disclosure was observed in the corporate governance and Shariah compliance dimensions, including the management of zakat and benevolent (qard al-hasan) funds as forms of accountability to Allah and society. In contrast, the environmental dimension demonstrated the lowest level of disclosure, with most indicators related to green banking, Environmental, Social, and Governance (ESG), energy efficiency, and sustainability remaining undisclosed.